Początki i rozwój jujitsu w II Rzeczypospolitej = The beginning and evolution of the jujitsu in the II Republic of Poland - Bębenek, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this article is to present events that led to the occurrence of martial arts on Polish lands in chronological order and in particular, to present the circumstances of the introduction of martial arts in Poland. Author attempts to determine why jujitsu was first and why. Reader is also shown the differences between martial arts and its sporting variation. The study covered the period from the beginning of the twentieth century until finished The II Republic of Poland and outline the shape and character of martial arts in our country.
Keywords: sztuki walki; judo; jujitsu; jujutsu; Daleki Wschód; Japonia; Polska; martial arts; Far East; Japan; Poland